SISTEM PENYELENGGARAAN TUTORIAL TATAP MUKA DI KABUPATEN TANGERANG - Dewi Andriyani; Wahyuni Kadarko (Jurnal Pendidikan, 2011)
This article is the result of research on face-to-face tutorial services for students participating in distance education programs. The research was conducted during the months April to June 2009 in tutorial centers in the district of Tangerang located at SMPN XIII and SD Sukasari 1. Subjects were participants of primary school teacher training program (PGSD), tutors, managers and organizers of the program. Observations focused on the administrative services, academic services, and facilities for tutorial activities. Results showed that there was no special briefing for participants. As a result many students are not prepared to follow the tutorial. The location viewed from the perspective of affordability was very low, because most students live in the suburbs. Tutorial classroom conditions do not meet minimum service standards of a conducive learning space as a result tutors were difficult to develop an instructional system optimally. It is advisable to give a special briefing for the students so that participants had an understanding of the nature of the tutorial, the need to increase the quality of facilities and infrastructure, review the location of activities, and the need for strict academic requirements for tutors.